Design and realization of quasi Yagi antenna for indoor application with 3D printing technology - Belen, Mehmet A.; Mahouti, Peyman (WILEY, 2018)
With the advances in the extrusion depositing base three-dimensional (3D) printing technology and decreases in their costs, these technologies are being used in many fields for fast and low cost prototyping means. One of these applications is manufacturing of microwave circuits. Herein, design and realization of quasi Yagi antenna for indoor application with 3D printing technology is presented. First, design of a wide band microstrip quasi Yagi antenna consists of a dipole fed by a coplanar strip line, a rectangular patch, and a ground reflector is studied. The size of the antenna is reduced by using a half bowtie shaped dipole and reflector. The studied microstrip quasi Yagi antenna is aimed to operate within the operation frequency range of 670-3000 MHz. Then for experimental results, the designed antenna is fabricated by using a 3D printer with poly(lactide acid) material. From observing the experiment results it can be concluded that 3D printed antenna has good performance, within the operation band with a good return loss characteristic performance of less than -10 dB and a moderate gain of 3.5-4.6 dBi. As it can be seen, the 3D printer technology is an efficient method for fast and accurate prototyping of antenna design.
Keywords: broadband antenna; 3D printer; indoor applications; microstrip antenna; quasi-Yagi antenna; Engineering; Optics